The Stagnation-Point Flow Over A Stretching Sheet In A Nanofluid - Md Rabi'e, Nur Farah Atikah (Enhanced Knowledge in Sciences and Technology, 2022)
This research is regarding a study on a stagnation-point flow over a stretching sheet in a nanofluid. Governing equations are transferred from partial differential equations into a set of nonlinear ordinary differential equations by using similarity transformation. The similarity equation is solved for three types of nanoparticles which are Au-Metallic, Copper Oxide and Carbon Nanotubes. Then, the equation is used to determine the numerical solution for velocity for stagnation-point flow over a stretching sheet in a nanofluid by using Runge Kutta Fehlberg 45 method (RKF45 Method). The velocity profiles are presented graphically and discussed. It is found that the inclusion of nanoparticles into the base water fluid has increased heat transfer coefficients and skin friction.